Interaction effect of rootstocks on gas exchange parameters, biochemical changes and nutrientstatus in Sauvignon Blanc winegrapes - Somkuwar, R. G.; Bhange, M. A.; Upadhyay, A. K.; Ramteke, S. D. (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
SauvignonBlanc wine grape was characterized for their various morphological, physiological and biochemical parameters grafted on different rootstocks. Significant differences were recorded for all the parameters studied. The studies on vegetative parameters revealed that the rootstock influences the vegetative growth thereby increasing the photosynthetic activities of a vine. The highest photosynthesis rate was recorded in 140-Ru grafted vine followed by Fercal whereas the lowest in Salt Creek rootstock grafted vines.The rootstock influenced the changes in biochemical constituents in the grafted vine thereby helping the plant to store enough food material. Significant differences were recorded for total carbohydrates, proteins, total phenols and reducing sugar. The vines grafted on1103-Pshowed highest carbohydrates and starch followed by 140-Ru,while the least amount of carbohydrates were recorded in 110-R and Salt Creek grafted vines respectively.Among the different rootstock graft combinations, Fercal showed highest amount of reducing sugar, proteins and phenols, followed by 1103-P and SO4, however, the lowest amount of reducing sugar, proteins and phenols were recorded with 110-R grafted vines.The vines grafted on different rootstocks showed changes in nutrient uptake. Considering this, the physico-biochemical characterization of grafted vine may help to identify particularrootstocks combination that could influence a desired trait in commercial wine grape varieties after grafting.